Profesionalisme Dakwah Dalam Pemberdayaan Masyarakat - Hendra, Tomi (Jurnal at-Taghyir, 2018)
Da'wah is a very noble activity, where a missionary interpreter seeks to convey the message of truth to the community, with the aim of inviting the community to be able to become better in life. The missionary activities are not only limited to the delivery of religious messages, but the activities of the missionary interpreter must be realized in the form of professionalism in preaching. Da'wah is not only concerned with the interests of the group but the common interest, from this point of view the professionalism of the missionary interpreter is highly demanded, so that it does not harm other parties as the target. In the community the missionary interpreter is not limited to conveying religious messages to the community at large, but a missionary interpreter must be able to play a role in community empowerment. By playing a role as an agent of empowerment, it will increasingly appear professionalism for a missionary interpreter. This paper is to find out how professional propaganda in community empowerment. A missionary interpreter has two important roles in community life; First, as a messenger of religious messages, secondly, as agents of empowerment for the community, so that with these two important roles Islam can be integrated into community empowerment by mixing all dimensions of people's lives in it.Keywords: Da'wah Professionalism in Community Empowerment.  Abstrak             Dakwah merupakan aktifitas yang  sangat mulia, dimana seorang juru dakwah berupaya menyampaikan risalah kebenaran kepada masyarakat, dengan tujuan mengajak masyarakat mampu menjadi yang lebih baik lagi dalam kehidupan. Aktifitas juru dakwah tidak hanya sebatas dari penyampai pesan-pesan agama, tetapi aktifitas juru dakwah ini harus diwujudkan dalam bentuk profesionalisme dalam berdakwah. Berdakwah tidak hanya mementingkan kepentingan golongan tetapi kepentingan bersama, dari sudut pandang inilah profesionalisme juru dakwah sangat dituntut, sehingga tidak merugikan pihak lain apa lagi masyarakat sebagai sasarannya. Dalam lingkungan masyarakat juru dakwah bukan sebatas dari menyampaikan pesan-pesan agama kepada masyarakat secara luas, tetapi seorang juru dakwah harus mampu berperan dalam pemberdayaan masyarakat. Dengan memainkan peran sebagai agen pemberdayaan, maka akan semakin tampak profesionalime seorang juru dakwah. Tulisan ini untuk mengetahui bagaimana propfesional dakwah dalam melakukan pemberdayaan masyarakat. Seorang juru dakwah memiliki dua peran penting dalam kehidupan bermasyarakat; Pertama, sebagai penyampai pesan-pesan agama, kedua, sebagai agen pemberdayaan bagi masyarakat, Sehingga dengan dua peran penting ini Islam bisa teintegrasi dalam pemberdayaan masyarakat dengan bercampur segala dimensi kehidupan masyarakat di dalamnya.Kata kunci: Profesionalisme Dakwah Dalam Pemberdayaan Masyarakat.